Feminism and a Vital Politics of Depression and Recovery - Fullagar, Simone; O'Brien, Wendy; Pavlidis, Adele (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Drawing upon insights from feminist new materialism the book traces the complex material-discursive processes through which women's recovery from depression is enacted within a gendered biopolitics. Within the biomedical assemblage that connects mental health policy, service provision, research and everyday life, the gendered context of recovery remains little understood despite the recurrence and pervasiveness of depression. Rather than reducing experience to discrete biological, psychological or sociological categories, feminist thinking moves with the biopsychosocialities implicated in both distress and lively modes of becoming well. Using a post-qualitative approach, the book creatively re-presents how women 'do' recovery within and beyond the normalising imperatives of biomedical and psychotherapeutic practices. By pursuing the affective movement of self through depression this inquiry goes beyond individualised models to explore the enactment of multiple self-world relations. Reconfiguring depression and recovery as bodymind matters opens up a relational ontology concerned with the entanglement of gender inequities and mental (ill) health.